Pemberdayaan Mahasiswa Pada Program Sekolah Orang Tua Hebat (SOTH) di Kecamatan Lakarsantri Surabaya - Dharmawan, Awan; Kabunggul, Orce (Apik Cahaya Ilmu, 2025)
This study aims to determine how student empowerment in the implementation of community service programs for great parents schools (SOTH) in Lakarsantri District, Surabaya City. In this study, the analysis used the Human Resource Development Theory Approach, with empowerment dimension indicators related to the title and using a descriptive qualitative approach method. Observations were made by conducting individual discussion methods on 4 informants who knew about the problems of SOTH activities. From the results of observations made related to the existing dimension indicators, namely: Ability Dimension; Fluency Dimension; Consultation Dimension; Cooperation Dimension; Guiding Dimension; Supporting Dimension, all show that Human Resource Development (HRD) through Empowerment of Surabaya Technology University (UTS) students in SOTH 2025 activities in Lakarsantri District, Surabaya City, has been carried out optimally and is expected to be able to make SOTH activities a success.